RICOEUR’S METHOD AND THEOLOGICAL SELF-UNDERSTANDING - Singsuriya, P. (Acta Theologica, 2019)
Paul Ricoeur is a prominent French philosopher and theological thinker whose enormous body of works has exerted influences in what David Tracy calls “theological self-understanding”. An understanding of Ricoeur’s method plays an important role in this regard. This paper, therefore, pays exclusive attention to an effort to understand his method or style of thinking. An overall synthesized picture of the method is given on the basis of analyses and observations of Ricoeurian scholars. The result of the synthesis portrays a picture of Ricoeur’s method as that of mediation through a long and winding detour. It is characterised as being dialectical, hybrid, and grafting. Illustrations are given of how his dialectical style of thinking assists theological self-understanding.